Trends in Human Resource Management and Organizational Behavior - Armin Amri (Economics and Digital Business Review, 2024)
This literature review aims to explore the trends shaping human resource management (HRM) and organizational behavior, focusing on digital transformation, remote work, employee well-being, diversity and inclusion, and strategic HRM. Using a systematic approach, relevant articles were selected from academic databases and analyzed to identify significant patterns and insights. The review synthesizes recent research to highlight key findings, emerging themes, and gaps in the literature. The findings indicate that digital transformation, driven by technologies such as AI and big data, is revolutionizing HR functions by enhancing efficiency and decision-making. Remote work and hybrid models, accelerated by the COVID-19 pandemic, have shown to improve job satisfaction and productivity but pose challenges in maintaining organizational culture. Employee well-being and mental health have gained prominence, with organizations implementing various initiatives to support holistic health, which positively impacts engagement and retention. Diversity and inclusion are critical for fostering innovation and competitive advantage, yet challenges such as unconscious bias and structural inequalities remain. Strategic HRM aligns HR practices with organizational goals, leveraging advanced technologies for competitive advantage and adaptability. The implications suggest that organizations must embrace technological advancements, promote flexible work arrangements, invest in employee well-being, and develop inclusive cultures to remain competitive. Further research is needed to address the evolving challenges and to provide comprehensive strategies for diverse organizational contexts. This review contributes to the understanding of how contemporary trends are reshaping HRM and offers a foundation for future studies aimed at enhancing organizational performance through strategic HR practices.